Metaverse Broadcasting: Enhancing News Item Text Comprehension Among Twelfth Graders - Trisnawati (Nusantara Science and Technology Proceedings, 2024)
Technology integration in education has opened new avenues for innovative teaching approaches. This study explores the integration of metaverse broadcasting to enhance news item text comprehension among Grade 12 IPA 3 students at Man Insan Cendekia Gorontalo. The respondents are 18 students. The research investigates its impact on student motivation, engagement, and comprehension. Using an experimental approach, the study compares traditional methods with metaverse broadcasting. The result shows that the average score before intervention was 71 to 84.72 after intervention. Metaverse broadcasting has proved that interactive learning through the metaverse improves motivation, engagement, and understanding. The study highlights the potential of immersive technology to enhance learning outcomes. this research underscores the potential of metaverse broadcasting as an effective educational tool for enhancing news item text comprehension. The findings demonstrate that interactive and immersive technology motivates students and significantly impacts their engagement and comprehension levels. This study contributes to the growing body of research on technology-enhanced learning methods and provides insights into their practical application in the classroom.